PENINGKATAN PEREKONOMIAN ACEH MELALUI SEKTOR PERTANIAN: ANALISIS TABEL INPUT OUTPUT TAHUN 2012 - Nuri Rosmika (JURNAL EKOMBIS, 2020)
This study aims the strategy to increase the agricultural sector of Aceh. With analize the Aceh's  input output table, it seen that the agricultural sector has a multiplier effect 1.30 on Aceh's economic growth; 0.27 to increase household income; and 0.47 on employment. Based on the simulation results, if there is an increase in government spending by 5 percent to the agricultural sector, there will be an economic growth 0.00570 percent, an increase in household income  0,00018 percent, and an increase in employment absorption 0.00004 percent. However, if there is an increase in investment in the agricultural sector by 5 percent, an increase in output of economic growth will be seen by 0.08797 percent, additional household income 0.00271 percent, and an increase in employment 0,00035. This indicates that the APBD allocated to investment in the agricultural sector is key to Aceh's efficient economic growth and effective poverty reduction through employment. Therefore, if the government wants to increase the output of the agricultural sector, it can be done by investing in this sector in the form of improving technology through the distribution of agricultural equipment such as tractors, rice thresher machines and the construction of irrigation.Keywords: APBD, Investment, Economy, Output Input Table, Agriculture Sector.